Influence of the optical switch’s extinction ratio on the crosstalk in fiber-optic seismometer array - Fei LIU; Xian ZHOU; Min ZHANG (物联网学报)
Optical switch is one of the key components in the time-division multiplexing fiber-optic seismometer array and has significant influence on the crosstalk of the array.The source of crosstalk in the array was analyzed based on differential delay heterodyne demodulation scheme.The expression of crosstalk appearing in the seismometer’s output was deduced with the limited extinction ratio.Via simulation, the relationship between the extinction ratio of optical switch and the seismometer’s crosstalk was presented under different array scales, i.e.basically the crosstalk decreases linearly with the increase of optical switch’s extinction ratio, and increases linearly with the increase of the array scale.Finally, an 8-element fiber-optic seismometer array was set up in the experiment, on which different optical switches (acousto-optic modulator and electro-optic modulator) owning distinct extinction ratios could be applied to generate pulse light.Experimental results verified the theoretical analysis as well as the simulation results.